Досвід викладання технічних дисциплін англійською мовою: виклики і рішення - Фурманова, Н. І.; Фарафонов, О. Ю.; Малий, О. Ю.; Furmanova, Nataliia; Farafonov, Oleksii; Malyi, Oleksandr (НТУ ДП, 2023)
У роботі описано досвід викладання технічних дисциплін для українських студентів англійською мовою. Окрема увага приділяється гейміфікації навчального процесу.

This work describes the experience of teaching technical disciplines for Ukrainian students in English. Special attention is paid to the gamification of the educational process.
Teaching technical disciplines in english: challenges and solutions
Keywords: English as a Medium of Instruction; викладання; гейміфікація; ігровий підхід; teaching; gamification; game approach